Crystal structure of 6-(quinolin-8-yl)benzo[a]phenanthridin-5(6H)-one, C26H16N2O - Li Chuan-Jun (Zeitschrift für Kristallographie - New Crystal Structures)
C26H16N2O, monoclinic, P21/c (no. 14), a = 12.3329(2) Å, b = 12.9276(2) Å, c = 12.11250(10) Å, β = 114.047(2)°, V = 1763.55(5) Å3, Z = 4, Rgt(F) = 0.0416, wRref(F2) = 0.1137, T = 293(2) K.